Dual mode grating sensor using microring conjugate mirror and plasmonic island. Issue 10 (26th September 2018) - Pornsuwancharoen, Nithiroth; Jalil, Muhammad Arif; Amiri, Iraj S.; Ali, Jalil; Yupapin, Preecha
Abstract: In this study, we propose a model for the dual mode gold grating sensor using a microring conjugate mirror (MCM) and the plasmonic island. The sensor measurement of derived quantity is the change in the Bragg wavelength and electron mobility that can be related to the optical phase‐shift or gold grating mobility changes. The plasmonic island consists of the stacked layers of silicon‐graphene‐gold materials. At the resonant condition, the gold electron mobility is driven by the whispering gallery mode generated by the nonlinear microring resonator. Additionally, the 3D reflection power profile of the grating sensor and target source interaction can be formed by the MCM. By selecting the suitable parameters, it can be arranged to have the four‐wave mixing output, which is the criterion of the 3D output of the MRC. The calculation results have shown that there is a relationship between the change in the electron mobility and Bragg wavelength of ~ 1.5 × 10 −21 cm 2 V −1 s −1 (mW) −1 at the λ Bragg of 1.55 μm, where the separation of 1 nm is obtained. The related mathematical formulas are re‐arranged for suitable applications.